Diversity in matrilineages among the Jomon individuals of Japan - Fuzuki Mizuno; Yasuhiro Taniguchi; Osamu Kondo; Michiko Hayashi; Kunihiko Kurosaki; Shintaroh Ueda (Taylor & Francis Group, 2023)
Background The Jomon period of Japan is characterised by a unique combination of sedentary and hunting/gathering lifestyles, spanning for more than 10,000 years from the final Pleistocene to the Holocene. The transition from the preceding Palaeolithic period to the Jomon period is known to have begun with the appearance of pottery usage. However, knowledge of the genetic background of the Jomon people is still limited. Aim We aimed to determine the population-scale complete mitogenome sequences of the Initial Jomon human remains and compare the occurrence of mitochondrial haplogroups in the Jomon period from temporal and regional perspectives. Subjects and methods For human remains dated to 8200-8600 cal BP, we determined their complete mitogenome sequences using target enrichment-coupled next-generation sequencing. Results We successfully obtained the complete mitogenome sequences with high depth of coverage and high concordance on consensus sequences. These sequences differed by more than three bases each, except for two individuals having completely identical sequences. Co-existence of individuals with haplogroups N9b and M7a was first observed at the same archaeological site from the Initial Jomon period. Conclusion The genetic diversity within the population was not found to be low even in the Initial Jomon period.